A General Method for Constructing Two-Dimensional Layered Mesoporous Mono- and Binary-Transition-Metal Nitride/Graphene as an Ultra-Efficient Support to Enhance Its Catalytic Activity and Durability for Electrocatalytic Application - Liu, B.; Huo, L.; Si, R.; Liu, Jian; Zhang, J. (American Chemical Society, 2016)
© 2016 American Chemical Society. We constructed a series of two-dimensional (2D) layered mesoporous mono- and binary-transition-metal nitride/graphene nanocomposites (TMN/G, TM = Ti, Cr, W, Mo, TiCr, TiW, and TiMo) via an efficient and versatile nanocasting strategy for the first time. The 2D layered mesoporous TMN/G is constituted of small TMN nanoparticles composited with graphene nanosheets and has a large surface area with high porosity. Through decoration with well-dispersed Pt nanoparticles, 2D layered mesoporous Pt/TMN/G catalysts can be obtained that display excellent catalytic activity and stability for methanol electro-oxidation reactions (MOR) and oxygen reduction reactions (ORR) in both acidic and alkaline media. The 2D layered mesoporous binary-Pt/TMN/G catalysts possess catalytic activity superior to that of mono-Pt/TMN/G, graphene free Pt/TMN, Pt/G, and Pt/C catalysts. Encouragingly, the 2D layered mesoporous Pt/Ti0.5Cr0.5N/G catalyst exhibits the best electrocatalytic performance for both MOR and ORR. The outstanding electrocatalytic performance of the Pt/Ti0.5Cr0.5N/G catalyst is rooted in its large surface area, high porosity, strong interaction among Pt, Ti0.5Cr0.5N, and graphene, an excellent electron transfer property facilitated by N-doped graphene, and the small size of Pt and Ti0.5Cr0.5N nanocrystals. The outstanding catalytic performance provides the 2D layered mesoporous Pt/Ti0.5Cr0.5N/G catalyst with a wide range of application prospects in direct methanol fuel cells in both acidic and alkaline media. The synthetic method may be available for constructing other 2D layered mesoporous metal nitrides, carbides, and phosphides.